The level of cognitive and behavioral representation gender consideration among trainee teachers in Morocco - Chaouqui, Mohamed; Bezrhoud, Hassnae; Erragragui, Mohamed; Azelmad, Khalid; Mellouki, Abdelhafid; Rahmani, Jamila; Ammi, Omar Ben (Frontiers in Education, 2025)
This study aims to establish a baseline understanding of the concept of gender and its specificities among trainee teachers in the Marrakech and Oujda regional Centers for Education and Training in Morocco. Using a descriptive and analytical approach, data were collected via an electronic questionnaire distributed among trainee teachers from these two Centers. The analysis focused on both cognitive and behavioral representations of gender, exploring trainee teachers’ perceptions, attitudes, and responsiveness to gender considerations in school settings. Methodological accuracy was respected as much as possible through a rigorous design of the questionnaire, data validation processes, and systematic cross-referencing of responses. The findings highlight three major themes. First, an average level in understanding the concept of gender and its cognitive representation. Second, divergent opinions that revealed differences in cognitive perceptions of gender-related concepts, and third, a strong consensus on the importance of adopting gender-responsive teaching practices and developing behaviors that support gender equity in the classroom. This research is significant in the Moroccan cultural and educational context, where Regional Teacher Training Centers play a crucial role in preparing future educators to address gender disparities effectively and foster inclusive educational environments.